Plasma membrane and cytoplasmic compartmentalization: A dynamic structural framework required for pollen tube tip growth - Fritz, Carolin; Reimann, Theresa; Adler, Jeremy; Knab, Johanna; Schulmeister, Sylwia; Kriechbaum, Choy; Müller, Sabine; Parmryd, Ingela; Kost, Benedikt (Plant Physiology, 2024)
Rapid, unidirectional pollen tube tip growth is essential for fertilization and widely employed as a model of polar cell expansion, a process crucial for plant morphogenesis. Different proteins and lipids with key functions in the control of polar cell expansion are associated with distinct domains of the plasma membrane (PM) at the pollen tube tip. These domains need to be dynamically maintained during tip growth, which depends on massive secretory and endocytic membrane trafficking. Very little is currently known about the molecular and cellular mechanisms responsible for the compartmentalization of the pollen tube PM. To provide a reliable structural framework for the further characterization of these mechanisms, an integrated quantitative map was compiled of the relative positions in normally growing Nicotiana tabacum (tobacco) pollen tubes of PM domains (i) enriched in key signaling proteins or lipids, (ii) displaying high membrane order, or (iii) in contact with cytoplasmic structures playing important roles in apical membrane trafficking. Previously identified secretory and endocytic PM domains were also included in this map. Internalization of regulatory proteins or lipids associated with PM regions overlapping with the lateral endocytic domain was assessed based on brefeldin A treatment. These analyses revealed remarkable aspects of the structural organization of tobacco pollen tube tips, which (i) enhance our understanding of cellular and regulatory processes underlying tip growth and (ii) highlight important areas of future research.
Created from Fastlane, Scopus look-up